Odpowiedź :
Zróbmy tabelkę:
[tex]\begin{array}{|c|c|c|c|c|c|} p & q & \sim p & \sim q & \sim p\ \vee\ q & \sim q \Rightarrow (\sim p\ \vee\ q)\\0 & 0 & 1 & 1 & 1 & 1\\ 0 & 1 & 1 & 0& 1 & 1\\1 & 0 & 0 & 1 & 0 & 0\\1 & 1& 0 & 0 & 1 & 1\end{array}[/tex]
Widać stąd, że implikacja ma wartość logiczną 0 tylko dla p=1, q=0 i takie wartości należy wstawić do podpunktów a)-d)
pozdrawiam
[tex]p\Rightarrow q=0\Leftrightarrow p=1 \wedge q=0[/tex]
[tex]\neg q\Rightarrow (\neg p \vee q)=0[/tex]
Zatem
[tex]\neg q =1 \Rightarrow q=0\\\neg p\vee q= \neg p \vee 0=0\Rightarrow \neg p=0 \Rightarrow p=1[/tex]